Gambaran Deteksi Dini Masalah Kesehatan Jiwa Menggunakan Edinburgh Postnatal Depression Scale (Epds) Pada Ibu Hamil - Nur Muhibah; Dewi Ambarwati (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Mental health problems in pregnant women are 12.6% higher than mental health problems in postpartum women, which is only 10.1%. Therefore, government policy, as stipulated in Minister of Health Regulation No. 21 of 2021, explains that pregnant women are included in cluster 2 and must receive primary health care services, including early detection of mental health. Early detection of mental health is carried out using the EPDS instrument Edinburgh Postnatal Depression Scale(EPDS) which has been shown to be an effective screening tool for identifying pregnant women who may be at risk for depression.Describes the picture of early detection of mental health problems usingEdinburgh Postnatal Depression Scale(EPDS) in pregnant women in the Cimanggu II Health Center Working Area. Method:This research is a quantitative descriptive study. The population was 229 pregnant women. The sampling technique used wassimple random sampling and obtained 151 respondents who met the inclusion and exclusion criteria. The instrument in this study used the EPDS questionnaire. Data analysis was performed using univariate tests. Symptoms of depressive disorders in pregnant women in the Cimanggu II Community Health Center Working Area amounted to 18.5% of respondents. There were 28 out of 151 respondents who experienced symptoms of depressive disorders in pregnant women in the Cimanggu II Health Center Working Area.